2006
DOI: 10.1111/j.1365-2621.2006.01190.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of malt pretreatment on phytate and tannin level of two sorghum (Sorghum bicolor) cultivars

Abstract: The seeds of two cultivars of Sudanese sorghum (Sorghum bicolor), namely Wad Ahmed and Tabat, were germinated for 4 days to obtain 1-, 2-and 4-day-old malts. Sorghum malt (5% and 10%) was added to sorghum flour. The mixtures were incubated at 30°C with shaking for 30, 60, 90 and 120 min. Malting loss was very slight for both cultivars and for all incubation periods. Phytic acid and tannin contents were assayed for all treatments. The results revealed that phytate and tannin contents were significantly (P £ 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 20 publications
0
11
1
Order By: Relevance
“…Therefore, overall tannin content was increased. However, some researches reported that germination reduce the tannin content, this can be due to solubilisation by enzymes because germination promote the hydrolytic enzymes (DEWAR et al, 1997;IDRIS et al, 2006). In the present study, the results disagree with previous researches.…”
Section: Germination Increased Gaba Content Of Sorghum Seedscontrasting
confidence: 57%
“…Therefore, overall tannin content was increased. However, some researches reported that germination reduce the tannin content, this can be due to solubilisation by enzymes because germination promote the hydrolytic enzymes (DEWAR et al, 1997;IDRIS et al, 2006). In the present study, the results disagree with previous researches.…”
Section: Germination Increased Gaba Content Of Sorghum Seedscontrasting
confidence: 57%
“…Many researchers reported that malting decreased polyphenol content of various types of sorghum (Elmaki et al. , 1999; Idris et al. , 2006; Mohamed Nour et al.…”
Section: Resultsmentioning
confidence: 99%
“…The polyphenol content for both genotypes was also significantly (P £ 0.05) decreased with fermentation of malted samples, and the reduction exceeded 55% for both genotypes. Many researchers reported that malting decreased polyphenol content of various types of sorghum (Elmaki et al, 1999;Idris et al, 2006;Mohamed Nour et al, 2010). Moreover, fermentation of malted sorghum samples caused further reduction in polyphenols (Abdelhaleem et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2002). Elimination or inactivation of such antinutritional compounds is absolutely necessary to improve the nutritional quality of sorghum and effectively utilise its full potential as food or feed (Idris et al. , 2006).…”
Section: Introductionmentioning
confidence: 99%